Blood pressure levels and body mass index in Brazilian adults with Down syndrome - Pucci, Felipe; Machado, Guilherme; Solera, Edcarlo; Cenovicz, Fernanda; Arruda, Christian; Braga, Chiu; Nisihara, Renato (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Increased life expectancy among people with Down syndrome (DS) has introduced new environmental factors that may affect blood pressure (BP) and/or lead to obesity in this population. The aim here was to investigate BP levels and body mass index (BMI) in adults with DS, correlating these data with the patients’ sex and age. DESIGN AND SETTING: Analytical cross-sectional observational study conducted in special schools in Curitiba (PR), Brazil. METHODS: 97 adult patients were included. BP was measured in accordance with the established guidelines. BMI was calculated by dividing the weight by the height squared (kg/m2 ). RESULTS: Sex had no influence on BMI; nor did systolic BP (SBP) or diastolic BP (DBP). The age range was from 18 to 56 years. No correlation was observed between increasing age and greater BMI or BP. Eighty-six individuals (88.7%) presented normal BP, eleven (11.3%) prehypertension and none hypertension. Twenty patients (20.4%) presented BP lower than 90 × 60 mmHg. BMI ranged from 18 to 48 kg/m2 (mean of 28.8 ± 3.92 kg/m2 ): 21.9% had normal weight; 40.7% were overweight; and 25.3% had obesity class I, 9.9% class II and 2.2% class III. Higher BMI was associated with significantly greater SBP and DBP (P = 0.0175 and P = 0.0015). CONCLUSION: Sex and age did not influence SBP, DBP or BMI in Brazilian adults with DS. Higher BMI was associated with greater BP (both systolic and diastolic).